A radical relational agency: Foucault, complexity theory and environmental resistances - Picard, E. Kezia (2010)
The aim of this thesis is to examine a radical relational agency, applied to contemporary environmental resistances, that incorporates both the thought of Michel Foucault and complexity theory. While Foucault’s thought, following from his argument that power is a relation, implies a relational agency, it does not, however, account for the agency of nonhumans and environments. Because power is a relation and not a possession, it can no longer be viewed as an attribute of individual subjects. Similarly, a relational agency is defined as an aspect of power relations. Complexity theory, on the other hand, acknowledges that humans interact with nonhumans and environments, but does not acknowledge that all relations are relations of power. In addition to Foucault’s explanation of power relations, complexity theory explicitly describes the processes of self-organization through which individual and diverse agents interact and change can emerge. Thus, a radical relational agency is defined as an aspect of the power relationships between many diverse agents. Change, according to both Foucault and complexity theory, happens nonlinearly. As a result, it often occurs unpredictably. However, change within complex systems is also limited by previous historical emergences. In this sense, both possibility and risk are inherent in the relationships between humans, nonhumans and environments. Indeed, I argue that a radical relational agency occurs because there are both possibilities and risks generated within ecological relations and relations of power. Therefore, I argue that any environmental action must account for the unpredictability inherent to the complex interactions between humans, nonhumans and environments.